Mercury Content in Impacted Wisdom Teeth from Patients of the Legnica–Głogów Copper Area—An In Vitro Pilot Study - Sadri Rayad; Maciej Dobrzyński; Amadeusz Kuźniarski; Marzena Styczyńska; Dorota Diakowska; Tomasz Gedrange; Sylwia Klimas; Tomasz Gębarowski; Marzena Dominiak (Journal of Xenobiotics, 2023)
The aim of this study was to determine the content of mercury in impacted third molars from Legnica–Głogów Copper Area residents to emphasize the effects of environmental pollution on the human body. A group of 72 patients with an average age of 27.3 ± 6.9 years participated in the study. Within this study, the research group (Legnica–Głogów Copper Area residents) comprised 51 individuals, while the control group (residents of Wrocław) consisted of 21 participants. A higher number of female individuals participated in the research (55). The amount of mercury present in the samples was determined through atomic absorption spectrometry with the use of a SpectraAA atomic absorption spectrometer and a V2 AA240FS flame attachment that utilized an air–acetylene flame. The accumulation of Hg in the teeth of members of the control group residing in Wrocław was studied, with a focus on identifying the risk factors that contribute to this phenomenon. The final model analyzed the presence of various factors, including thyroid and parathyroid gland diseases, cardiac diseases, and interval-scale Vit. D3 concentration. Among these factors, the presence of cardiac diseases was deemed statistically significant in relation to an increase in Hg concentration in third molars (rate ratio = 2.27, p < 0.0001). The concentration of mercury increased with the age and time of residence in the L-G Copper District.